RAB20 deficiency promotes the development of silicosis via NLRP3 inflammasome - Peng, Zhouyangfan; Duan, Mingwu; Zhao, Kai; Tang, Yiting; Liang, Fang (Frontiers in Immunology, 2022)
Silicosis is a worldwide serious occupational diseases that caused by inhalation of silica crystals. However, the pathogenesis mechanism of silicosis is little known. We performed single-cell sequencing in bronchoalveolar lavage fluid (BALF) from mine workers with silicosis and their co-workers who did not develop silicosis, and found that the RAB20 deficiency in monocytes/macrophages was strongly linked with the development of silicosis. In the silicosis murine model, RAB20 knockout markedly enhanced the silica crystals-induced pulmonary interstitial fibrosis and respiratory dysfunction. Besides, this process is strongly accompanied with IL-1β release and NLRP3 activation. In vitro, RAB20 knockout macrophages aggravated the crystalline silica-induced IL-1β release and NLRP3 inflammasome activation partly by increased ratio of crystalline silica/phagosomal areas/volumes to induce lysosomal injury. Thus, these findings provide novel molecular insights into the intricate mechanisms underlying lysosomal protein RAB20 is necessary for environmental irritants-mediated innate immunity, and shed light on the future development of novel therapy target for the prevention of silicosis.